2004
DOI: 10.1016/j.chembiol.2004.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biosynthesis of the Jamaicamides, New Mixed Polyketide-Peptide Neurotoxins from the Marine Cyanobacterium Lyngbya majuscula

Abstract: A screening program for bioactive compounds from marine cyanobacteria led to the isolation of jamaicamides A-C. Jamaicamide A is a novel and highly functionalized lipopeptide containing an alkynyl bromide, vinyl chloride, beta-methoxy eneone system, and pyrrolinone ring. The jamaicamides show sodium channelblocking activity and fish toxicity. Precursor feeding to jamaicamide-producing cultures mapped out the series of acetate and amino acid residues and helped develop an effective cloning strategy for the bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
539
0
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(565 citation statements)
references
References 67 publications
11
539
0
7
Order By: Relevance
“…This means that the bromination reaction either takes place while the substrate is attached to JamC or otherwise on one of the other NRPS or PKS proteins found on the jamaicamide biosynthetic pathway or after the jamaicamide is fully assembled. 5-Hexanoic acid and 5-hexynoic acid were also alternative substrates, in agreement with the classical pyrophosphate exchange assay (39).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This means that the bromination reaction either takes place while the substrate is attached to JamC or otherwise on one of the other NRPS or PKS proteins found on the jamaicamide biosynthetic pathway or after the jamaicamide is fully assembled. 5-Hexanoic acid and 5-hexynoic acid were also alternative substrates, in agreement with the classical pyrophosphate exchange assay (39).…”
Section: Discussionsupporting
confidence: 84%
“…To illustrate that this method was not only valid for NikP1, the substrate loading for the following systems were examined: the CloN5/CloN4 carrier/adenylation domain pair involved in the formation of clorobiocin (Table 1) (5), CouN5/CouN4 involved in the formation of the antibiotic coumermycin (5), EntB(ArCP)/EntE involved in the formation of the siderophore enterobactin (24), HMWP2, involved in the formation of the siderophore yersiniabactin (27), PchE/PchD involved in the biosynthesis of the siderophore pyochelin (38), JamC/JamA involved in the formation of the neurotoxin jamaicamide (39), and two NRPS modules from the orphan NRPS/PKS gene cluster on Bacillus subtilis for which the product is unknown (40,41,42). The adenylation-carrier di-domains analyzed are from PksN (BG12652) and the second NRPS module from PksJ (BG10929, gene annotation from http://genolist.pasteur.fr/SubtiList/.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the HMGS-type gene pedP, several other genes were identified that putatively participate in exomethylene bond biosynthesis. Evidence for the role of PedL, PedM, and PedN in this pathway comes from the comparison of gene clusters involved in the biosynthesis of polyketides with ␤-branches, including mupirocin (23), the antibiotic TA (33), leinamycin (34), and the jamaicamides (35). All gene clusters contain a conserved, clustered set of genes encoding an HMGS, a variable number of CR genes (usually described as enoyl-CoA hydratases but most likely catalyzing different reactions), and a monofunctional KS and ACP.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of conserved catalytic motifs in the related methyltransferases shows that none of the metazoan FASs contains an intact set of catalytic residues, in agreement with the observation that these enzymes do not methylate their products and are not SAM-dependent. However, in related fungal and bacterial polyketide synthases, intact homologues of this domain are found in equivalent positions and are leading to the production of (partially) methylated products (Edwards et al 2004 ;Fujii et al 2005 ;Molnar et al 2000). The significance of the yME domain for animal FAS remains unclear ; it is probably a remnant from an evolutionary precursor multienzyme producing branched fatty acids or polyketides, and it may still play a steric or stabilizing role for the overall functioning of the enzyme.…”
Section: Domain Structuresmentioning
confidence: 99%